The Relationship of Teachers’ Perception Towards Their Leadership Capacity and Their Level of Job Satisfaction in An International School in Bangkok - Braly, Bruce; Ye, Yan (Scholar: Human Sciences, 2018)
The purpose of this research was to study the relationship of the teachers’ perception towards their leadership capacity and their level of job satisfaction in an international school in Bangkok during the academic year 2016-2017. This researcher used the high capacity leadership instrument adopted from Pierce (2007) based on Lambert’s (2003) leadership capacity school survey (LCSS), as well as the job satisfaction survey adopted from Drukpa (2004). The results showed there was a significant relationship between the teachers’ perception towards their leadership capacity and their level of job satisfaction in this international school. The correlation analysis result showed there was a strong positive relationship between teachers’ perception towards their leadership capacity and their level of job satisfaction. The findings were discussed and the research confirmed that sustained school improvement can be facilitated with increased teacher leadership capacity resulting in increased levels of job satisfaction among teachers as they experience improved student outcomes. The study recommended the school leaders and teachers to sustain and further develop their leadership capacity and skills so as to maintain the high level of job satisfaction.